Measuring The Acceptance Level of User Interface Design of ERP System at PT Allure Alluminio Using Technology Acceptance Model (TAM) Method - Mutoriq, Alfat; Purwinarko, Aji (Journal of Advances in Information Systems and Technology, 2023)
The utilization of information technology and the internet in the industry is generally done through the implementation of Enterprise Resource Planning (ERP) systems to manage business processes. The success of ERP system implementation requires efforts to support and prevent failure risks. One of the risk factors for failure is the User Interface (UI) design of the ERP system. Good UI design that meets user needs needs to be considered. This research utilizes the Design Thinking (DT) method to create a good UI design and the Technology Acceptance Model (TAM) method to measure the acceptance of UI design in the manufacturing module of PT Allure Alluminio. The DT method was chosen as the UI design method for the ERP system because it is considered more creative in generating product concepts compared to other standard methods and TAM was chosen as one of the best methods for explaining technology acceptance and is a popular and commonly used approach. The UI design process is carried out in 6 phases of DT under the guidance of the Person in Charge (PIC), and the acceptance of UI design is measured after system implementation. Acceptance measurement is conducted using TAM with navigation and UI design variables as external variables, which are taken from previous research, and it tests the variables of Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Behavioral Intention to Use (BITU) among 50 users of the ERP system in the manufacturing module at PT Allure Alluminio through a Google Form questionnaire. The collected data is analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 3.2.9. The research results indicate that the DT method is effective for UI design as it involves users. The analysis shows that the use of ERP systems is influenced by perceived usefulness and ease of use, but not influenced by UI design. Navigation and UI design provide ease of use.